Detection of rabies virus in organs of bats of genus Artibeus by means of hemi-nested RT-PCR and real time RTPCR techniques - Scheffer, K. C.; Fahl, W. O.; Iamamoto, K.; Carnieli Jr., P.; Carrieri, M. L.; Oliveira, R. N.; Ito, F. H. (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2013)
Molecular techniques have been used increasingly as tools for the diagnosis by detecting the rabies virus genome. This study aimed to detect the presence of rabies virus in the wash of skull and in different organs of the genus Artibeus bats using the hemi-nested RT-PCR (hnRT-PCR) and Real Time RT-PCR molecular techniques. From approximately 4,000 specimens of bats received at the Institute Pasteur for rabies diagnosis, 30 bats of the genus Artibeus were selected, with records of positive results for rabies by the traditional techniques of direct fluorescent antibody test (FAT) and inoculation of murine neuroblastoma cell line (N2A). Salivary glands, urinary bladders, kidneys, lungs, and also the washes of the skullcaps of the specimens were collected. The scraping of the skull was performed with the aid of sterile pipette tips and then washed with 1,000μL diluent composed of 0.85% saline solution, supplemented with 2% Bovine Fetal Serum, free of rabies virus specific antibodies and containing 0.1% Gentamicin Sulfate. The urinary bladders were diluted using the same diluent mentioned above, to 1:20 (w/v) and other organs were diluted 1:10 (w/v). The extraction of total RNA was carried out using the TRIzol® and the reverse transcription was followed by PCR and hnRT-PCR using primers specific for the gene encoding the N protein. From the product derived by the reverse transcription, the Real Time RTPCR technique was run by using primers and probes specific for the antigenic variant 3 of rabies virus. When evaluated the total samples analyzed, the overall results of the sensitivity for both the hnRTPCR and Real Time RT-PCR techniques was 86%. A comparison between the hnRT-PCR and Real Time RT-PCR techniques performed by Fisher’s exact test has revealed that the proportion of positives detected for the washing of the skull was similar to that of the organs examinations (P> 0.05). In relation to the positive results found in hnRT-PCR and Real Time RT-PCR techniques were 100% in brain washes, 90% and 93.33% in the salivary glands, 83.33% and 90% in urinary bladders, 80% and 93.33% in kidneys, and 76.67% and 50% in lungs. These results suggest that both the hnRT-PCR and the Real Time RTPCR techniques can be used as complementary methods for the rabies diagnosis and the techniques are sensitive enough for use in studies of pathogenesis. The Real Time RT-PCR technique performed in this study proved effective in detecting the rabies virus in different organs and extra neural tissues with the advantage of being a faster and more sensitive procedure.